Solve:2m-3/3=3m+1/6
Answers
Answered by
0
Answer is m = -1/3
I hope it helps you.
Attachments:
![](https://hi-static.z-dn.net/files/db4/826b922a61bc94ac0a425281045fde34.jpg)
Answered by
1
Answer:
value of m = 7.
Step-by-step explanation:
(2m -3)/3 = (3m + 1)/6
on cross multiplying we can get
6(2m -3) = 3(3m + 1)
12m -18 = 9m + 3
12m - 9m = 3 + 18
3m = 21
m = 21/3
m = 7
Similar questions
Math,
2 months ago
Math,
2 months ago
Physics,
2 months ago
CBSE BOARD X,
5 months ago
Biology,
1 year ago
Social Sciences,
1 year ago